Carta de los editores - García San José, Daniel; Llano Alonso, Fernando Higinio; Villegas Delgado, César Armando (IUS ET SCIENTIA, 2018)
Se incluye la carta de los editores (editorial Letter del Vol. IV, nº 2 de ius et scientia